Effect of medically lowering intraocular pressure in glaucoma suspects with high myopia (GSHM study): study protocol for a randomized controlled trial - Lin, Fengbin; Da Chen, Shi; Song, Yun He; Wang, Wei; Jin, Ling; Liu, Bing Qian; Liu, Yu Hong; Chen, Mei Ling; Gao, Kai; Friedman, David S.; Jonas, Jost B.; Aung, Tin; et al. (Trials, 2020)
Currently, whether and when intraocular pressure (IOP)-lowering medication should be used in glaucoma suspects with high myopia (GSHM) remains unknown. Glaucoma suspects are visual field (VF) defects that cannot be explained by myopic macular changes or other retinal and neurologic conditions. Glaucoma progression is defined by VF deterioration. Here we describe the rationale, design, and methodology of a randomized controlled trial (RCT) designed to evaluate the effects of medically lowering IOP in GSHM (GSHM study).
Gesehen am 11.08.2025